PSYCHOLOGICAL MEANINGS OF â€œPOSITIVE SPIRITUAL ENVIRONMENTâ€ AND â€œPLACES TO COMMUNICATE WITH GODâ€ - Barrera-Hernandez, Laura Fernanda; Corral-Verdugo, Victor; Tapia-Fonllem, Cesar Octavio; Fraijo-Sing, Blanca Silvia (European Scientific Journal, ESJ, 2015)
The spaces that surround and sustain daily life significantly influence peopleâ€™s way of thinking, feeling and behaving. They also reflect personal and meaningful aspects of their lives. This study was aimed at investigating conceptions regarding spiritual environments and characteristics of places wherein individuals communicate with God or a â€œhigher powerâ€, seeking to find empirical support to the idea of positive spiritual environments (spiritual contexts that, simultaneously, promote human wellbeing and environmental conservation). Ninety-one undergraduate students participated in the study. The network of spiritual environment generated a network size of 137 words with a core of 28 words. The highest semantic weights were produced by peace, God, tranquility, love, faith, church, pray, harmony, beliefs, wellbeing, happiness, and relaxation. Characteristics of the place wherein people communicate with God produced a network size of 104 words and a core of 27 words. The most important of those words were: church, home, calm, room, quiet, school, sacred, natural, alone, street, prayer, and clean. Few words communicating concern for environmentally conservation behaviors were found within the network.